Gamified Recruitment: A Way to Win the Talent of Tomorrow? - Martensen, Hannah; Martensen, Malte; Asanger, Johannes (Managerial Economics, 2023)
Organizations are faced with increased competition in the war for talent, and their sustained competitive advantage may depend on the ability to attract suitable candidates. The gamification of HR recruitment processes can be one solution, as it creates employer brand awareness and enables candidates to better assess their fit with the organizational culture and job requirements. Based on a comprehensive literature review and through focus groups and qualitative content analysis, we develop guidelines for effective application design and implementation. Our findings are mirrored against UTAUT 2 theory and consolidated in a Model for Acceptance of Gamified Recruitment Elements. Results suggest that gamified recruitment is an effective option to support traditional recruitment processes in orienting candidates and companies about the individual employer fit, ultimately increasing the quality of applications and strengthening organizations’ talent pools. From the results, we derive guidelines on how to effectively implement design features.